Realisasi Jual Beli Padi di Desa Benteng Barat Kecamatan Sungai Batang - Nurcahaya Nurcahaya; Hendro Lisa; Martina Napratilora (AL-Muqayyad, 2022)
The realization of the sale and purchase of rice carried out by the community by selling the rice before harvesting or still in the yellowing process and not yet suitable for harvesting. This study aims to find out how the realization of buying and selling is carried out and to find out how buying and selling in the perspective of Islamic economics is on the sale and purchase of rice in Benteng Barat Village. This type of research is qualitative research. The research subjects were farmers and rice farmers with 14 farmers and 4 rice farmers in Benteng Barat Village. While the object of research is the sale and purchase of rice in the perspective of Islamic economics. Data collection techniques are interviews and documentation. The conclusion of this study is the realization of buying and selling carried out is the same as other buying and selling, except that buying and selling is carried out before harvesting by cans or per kilo and rice will be delivered after harvest and buying and selling in the perspective of Islamic economics is still not in accordance with the principles of the Islamic economy. the principle of buying and selling in the perspective of Islamic economics, because there are still many principles that are violated, such as, the principle of God, the principles of benefit/benefit, the principles of ethics/morals and the principle of authenticity.